Adverse Impacts of Unethical Anthropogenic Activities upon the Teknaf Peninsula Ecologically Critical Area, Cox’s Bazar (Bangladesh Journal of Bioethics, 2020)
The coastal zone of Bangladesh is endowed with dynamic ‘Terrestrial’ and ‘Coastal and Marine ecosystem’. The zone confronts with declined environmental quality owing to unethical anthropogenic interventions. Few studies regarding ethical attitudes of local communities to conserve the coast were conducted earlier. Two objectives, such as (i) heavy metal concentration, and (ii) physio-chemical quality of sample soil and water were selected to reveal the environmental state of study area. Five heavy metals like- Cadmium, Copper, Iron, Lead, and Zinc; and four physio-chemical parameters such as, the pH, Electrical Conductivity, Temperature, and Turbidity of sample soil and water were measured. The average concentration of Pb in soil is 10 times higher than world average (0.03 mg/g), while Cd concentration in soil is two times more than world average (0.11 mg/L). The concentration of Fe at Inani beach water is 1.54 mg/g more than world average (3.4 mg/g). The physio-chemical parameters are within standard range. Unethical discharge of toxic effluents from shrimp hatcheries, and municipal garbage are main sources of pollution, which ensue into environmental degradations. Concentration of five heavy metals and Calcium Carbonate (CaCO3) in sample mollusk shells exhibit biodiversity deterioration. The mollusk shells from Inani beach contains 0.04 mg/L Cd,0.08 mg/L Cu, 0.42 mg/L Fe, 0.38 mg/L Pb, and  0.07 mg/L Zn. The CaCO3 content in mollusk shells at Inani beach is 49.5%, which indicates the degradation of the mollusks, as shells normally are made with 95% - 97% Calcium Carbonate. Hence, the Department of Environment (DOE), Bangladesh (GoB) declared the area as an ‘Ecologically Critical Area’ (ECA). The concerned stakeholders, like- CPP volunteers and officials, Forest Division, Fisheries Research Institute, Bangladesh Water Development Board, Union Chairman and Journalists of Cox’s Bazar recommended insertion of moral values among local stakeholders through trainings, motivational lectures, demonstrations and dramas, as well as, incorporation of lessons about consequences of unethical activities upon geo-environment into text books. Though least practice has been found regarding moral values during survey, the present research advocates in developing ‘Knowledge pool’ about coastal environment, creating awareness, and developing moral ethics among the local, regional and national stakeholders.